2018
DOI: 10.22159/ijpps.2018v10i12.28075
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Acute Oral Toxicity Profiling of the Methanolic Leaf Extract of Clinacanthus Nutans in Male and Female Icr Mice

Abstract: Objective: This study aims to investigate the sub-acute oral toxicity of a methanolic leaf extract of Clinacanthus nutans (MECN) in male and female mice.Methods: The study used three groups of male and female mice, the crude MECN was dissolved in distilled water and administered orally in single doses of 1000 and 2000 mg/kg body weight for 28 d by gavage, at a dosing volume of 10 ml/kg body weight, while the control group received only the distilled water. Mice were weighed weekly for the duration of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The safeties of the individual herbs of AA and BD are well known, but the combined effects of these herbs are unclear. Thus, it becomes essential to evaluate the safety and toxicity of the combination of these plants (BD&AA) [16]. This preparation consists of ingredients of herbal source which has been used as kidney protective agents.…”
Section: Discussionmentioning
confidence: 99%
“…The safeties of the individual herbs of AA and BD are well known, but the combined effects of these herbs are unclear. Thus, it becomes essential to evaluate the safety and toxicity of the combination of these plants (BD&AA) [16]. This preparation consists of ingredients of herbal source which has been used as kidney protective agents.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that the male and female mice showed no alteration of their body weight after administrated with the methanolic leaf extracts at 1,000 and 2,000 mg/kg. Besides, there were no hematological, biochemical, and histology signs of toxicity after 28 days (Abdulwahid et al, 2018).…”
Section: Plant Parts and Extracts Pharmacological Activities Referencesmentioning
confidence: 94%
“…On the contrary, a recent study had claimed that sub-acute administration of the extracts once at 2000 mg/kg induced mild hepatic and renal histological alterations in mice. Similarly, repeated daily oral administration of C. nutans leaves extract for 28 days induced mild to moderate hepatic degeneration at 500 mg/kg and renal necrosis at 1000 mg/kg in female ICR mice [ 74 , 75 ]. These polarized findings could be due to insufficient scientific studies being conducted previously; moreover, the majority of those experiments were done as preliminary and fundamentally oriented.…”
Section: Pharmacological and Medicinal Propertiesmentioning
confidence: 99%